TRANSFORMATION OF BUMDES HUMAN RESOURCES: FROM LOCAL MANAGERS TO RURAL ENTREPRENEURS IN THE AGE OF DISRUPTION - Jumardi; Jason Agustinus Priyogo Utomo; Efan James William Chendry; Monalisa; Afrizal Firman (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
A Village-Owned Enterprises (BUMDes) play a strategic role in rural economic development by managing local resources. However, the ongoing digital disruption, characterized by technological shifts, market volatility, and intensified competition, demands a fundamental transformation of the human capital within BUMDes. This study aims to analyze the capacity of BUMDes human resources in facing disruptive challenges, identify key enabling and inhibiting factors in their transformation from local managers to rural entrepreneurs, and formulate relevant and sustainable strategies for their development. Employing a quantitative approach, data were collected through structured questionnaires distributed to 40 BUMDes administrators across multiple regions. The analysis utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to assess the interrelationship between variables. The results revealed that digital skills significantly influence the readiness for role transformation, while managerial knowledge and innovation motivation did not show statistically significant effects. The study contributes theoretically by expanding the human capital framework in the context of rural development and offers practical insights for policy design related to structured digital training and mentoring programs. It alsoadvocates for a collaborative ecosystem involving local governments and development actors to support inclusive and sustainable rural entrepreneurship in the face of ongoing disruptions.